Evaluation of noise pollution in two initial education centers in the city of bluefields (Nexo Revista Científica, 2020)
At present, the growth of cities has brought about the increase of pollution of various types, among them the noise pollution generated by the excess of environmental noise. In the city of Bluefields there are several centers of initial education that are in the area of greater commercial activity of the locality. For this reason and the ignorance of the current levels of noise pollution in two of these centers, this research has been carried out in which the background ambient noise levels are measured inside and outside the San José Colleges and the Nicaraguan Association of Teachers of Nicaragua (ANDEN). A type 2 sound level meter was used to measure the noise levels with which the reverberation time (echo), word intangibility and acoustic discomfort were estimated. The measurements were carried out for a week in both centers at hours from 7:00 am to 12:00 md. The results showed that the indoor and outdoor noise levels in both centers exceed the permissible levels according to national and international legislation. The equivalent continuous noise level recorded at San Jose (92.83 dBA) and ANDEN (83.14 dBA) indicates that teachers and students are exposed to possible health problems that are expressed in stress and headaches. It is necessary to design a strategy to reduce the impact of noise through actions carried out between schools, local education authorities and the local municipality.